2011
DOI: 10.1007/s11695-011-0475-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obestatin, Ghrelin, and Inflammatory Cytokines in Obese Patients with Non-alcoholic Fatty Liver Disease

Abstract: This study suggests that products of the GHRL gene may be important for the pathogenesis of NASH and fibrosis. Additional confirmatory studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 44 publications
3
38
0
3
Order By: Relevance
“…108 However, in patients with NAFLD and hepatitis C, DAG and AG plasma levels are shown to be higher than in normal individuals. 109,110 In addition, in humans, it was suggested that ghrelin levels should be reduced in response to the development of insulin resistance rather than being influenced by liver damage per se. 111,112 In vivo, peripheral infusion of AG inhibits insulin-induced suppression of hepatic glucose production while stimulating overall glucose uptake in mice.…”
Section: Ghrelin and Livermentioning
confidence: 99%
“…108 However, in patients with NAFLD and hepatitis C, DAG and AG plasma levels are shown to be higher than in normal individuals. 109,110 In addition, in humans, it was suggested that ghrelin levels should be reduced in response to the development of insulin resistance rather than being influenced by liver damage per se. 111,112 In vivo, peripheral infusion of AG inhibits insulin-induced suppression of hepatic glucose production while stimulating overall glucose uptake in mice.…”
Section: Ghrelin and Livermentioning
confidence: 99%
“…Система грелин-обестатин участвует в патогенезе жиро-вой болезни печени (ЖБП) и фиброза печени [47]. У 75 больных ЖБП M. Estep и соавт.…”
unclassified
“…У 75 больных ЖБП M. Estep и соавт. [47] определяли уровень обестатина в сы-воротке крови и получили несомненное доказательство, что при ЖБП снижена секреция обестатина, причем это снижение гене-тически обусловлено. Система грелин-обестатин влияет на возникновение ЖКБ.…”
unclassified
“…In a recent publication by Estep et al [7], they report on the relation of the three ghrelin gene products (ghrelin, DAG, and obestatin) and their involvement in those metabolic and inflammatory pathways that are linked with the development of NAFLD. They studied 75 morbidly obese patients with biopsy-proven NAFLD (41 with histologic NASH) and found that patients with NASH had twofold higher concentration of DAG than patients with non-NASH.…”
mentioning
confidence: 99%
“…Ghrelin and obestatin concentrations positively correlated with fibrosis stage. Apparently, products of the ghrelin gene may be important for the pathogenesis of NASH and fibrosis [7].…”
mentioning
confidence: 99%